Fully Communication Oriented Information Modeling On SME Information Systems Development - Ela Nadila; Kemas Muslim Lhaksmana; Seno Adi Putra (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Information modeling a very important role in the development of information systems today. Information modeling is an activity to create a conceptual model that includes all significant information in business processes. Using information modeling, a machine is needed for implementation, and redundancy and anomaly problems are also common in databases. This problem arises when the database is not normalized. To solve the problem, this research will analyze the SME information system using the Fully Communication Oriented Information Modeling  (FCO-IM) method and compare it with the method without FCO-IM made by 12 designers. The results of the analysis, information modeling using FCO-IM method can produce a relational data schema that already meets 3NF normalization and is suitable for implementation in SME information system development so that it can be used as an option in data modeling and can avoid data redundancy problems.